Tax incentives are key to survival of Canadian mineral exploration - Kenneth A. Grace (Society for Mining, Metallurgy & Exploration, 1989)
Introduction The 1980s have not been kind to the mining industry, especially in the United States. As mineral commodities prices plunged, marginal producers were squeezed out and then major players were forced to cut back or close down operations. Base metal miners suffered the most. Gold was all that glittered. As had been the case throughout min¬ing's history, exploration activity was an early victim of these depressed conditions. Mining companies had to economize drasti¬cally and exploration was deemed a nones¬sential activity. Funding for new explora¬tion ventures dried up as mining was seen as a poor investment. A national magazine even proclaimed the death of the industry. Indeed, ignoring matters of independ¬ence of supply and the relationship of min¬eral production to national security, it was argued that mining was but a small cog in the overall scheme of things in the United States. The industry made a relatively small contri¬bution to the gross national output. We were becoming a service industry economy, re¬member? But what of those countries where mining plays a major role in the economic well-being? In some, mining is the national economy. In a few specific cases, special conditions actually brought prosperity. Copper production in Chile is one example. There, high grade copper, low production costs, and a technically advanced industry reaped the benefits of mine closures else¬where. In most other cases, however, par¬ticularly in the lesser developed countries, whole economies were devastated. This article will show what one major mineral producer, Canada, did to ensure the survival and even growth of its minerals exploration activity during these lean years. Background While Canada is among the world's mining leaders, mining is not its dominant industry. Still, it plays a far more important role than in the United States. It is a major earner of foreign exchange, currently accounting for about 25% of the total value of exports. Through spinoffs and a multiplying effect, it is a significant employer. In the far north, particularly, mining is the major nongovernment industry and a leading factor in the opening up of frontier territory. The industry cannot be allowed to die because it is often the main economic underpinning for vast, remote areas. Thus, exploration for new deposits cannot be cur¬tailed significantly without it having a long¬term negative impact on the very fabric that melds such a large, sparsely-populated ex¬panse of country into a nation. Over the years, Canadian governments have employed various means to encourage the development of new mines. Often, these incentives were tax-oriented, such as the three-year income tax holiday that applied to new mines in the 1950s and 1960s. The advantage of the tax connection is that any such incentive policy can be applied across the board to the 10 provinces and two territories that make up the federation of Canada. This is important because mining, except for the two federally-administered northern territories, comes under provincial government jurisdiction. Mining taxation is a complex give-and-take between the central and provincial authorities. In Canada, expenditure on mineral exploration is an allowable cost against reve¬nue for tax purposes. This works well pro¬vided there is some revenue from which to deduct. New exploration companies, those with no income from mining activities, de¬rive little benefit from this type of tax provi¬sion. Similarly, in times of depressed prices and reduced or nonexistent profits, the tax deductibility of exploration spending loses its value even for the major mining compa¬nies. To encourage exploration in Canada during the lean years, a different sort of incentive was required. The instrument used during the 1980s was again tax connected. It became known as flow-through financing or, simply, flow-through shares. When it assumed its final shape, it worked dramati¬cally. Flow-through shares Flow-through shares are so-named because they permit tax benefits earned by a corporation to 'flow-through' to the share¬holder. Basically, when an investor buys a flow-through share and the proceeds de¬rived by the company from this transaction are used for Canadian exploration, the in¬vestor can claim a deduction for tax pur¬poses as if the exploration expenditure was made by him personally. Flow-through shares go back to the early 1970s when Canada revamped its mineral income tax law. At that time, it permitted full deduction of exploration and development expenditures and provided for an automatic depletion allowance of one¬ third of operating profits from mining. There was also the three-year income tax holiday for new mines. New legislation replaced the depletion allowance with an earned depletion arrange¬ment whereby one dollar of depletion was earned for every three dollars spent on ex¬ploration and development. This earned depletion was `banked' during a transitional period (to 1974). After that it could be deducted from resource profits up to a maximum of 25% of such profits in any one year, with the excess carried forward. To promote exploration and mine de¬velopment in Canada, the earned depletion allowance plus the continued deductibility of exploration and development expendi¬tures permitted the recovery of risk capital before taxation. The three-year tax holiday, however, disappeared. Also, mining com¬panies that did not reinvest in exploration lost the depletion allowance benefit.